2020
DOI: 10.4067/s0718-27242020000400019
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Absorptive Capacity on Innovation in Peru

Abstract: This research aims to determine absorptive capacity's impact on innovation in SMEs in Peru. SMEs in Latin America tend to be characterized by technological backwardness, and innovations, if any, tend to be incremental in nature. In Peru, more than half of innovation activities are destined to the acquisition of capital goods. In this sense, rather than generate innovation, SMEs tend to adopt existing innovations. Thus, in order to reap the benefits of innovation adoption, SMEs must possess a high degree of abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
4
0
2
Order By: Relevance
“…Likewise, this study contributes to understanding the variables that affect innovation in companies, such as their absorptive capacity. This study provides empirical evidence in this regard, specifically in Colombian companies, contributing to the knowledge of absorptive capacity in Latin America, a subject that, as has been pointed out by other authors (e.g., Ortigueira-Sánchez et al, 2020; Zuñiga-Collazos et al, 2020), has so far been vaguely studied in the region.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Likewise, this study contributes to understanding the variables that affect innovation in companies, such as their absorptive capacity. This study provides empirical evidence in this regard, specifically in Colombian companies, contributing to the knowledge of absorptive capacity in Latin America, a subject that, as has been pointed out by other authors (e.g., Ortigueira-Sánchez et al, 2020; Zuñiga-Collazos et al, 2020), has so far been vaguely studied in the region.…”
Section: Discussionmentioning
confidence: 57%
“…They examined 116 small and medium-sized firms (SMEs) and demonstrated that when companies receive knowledge transference (an ACAP feature), they improve their position in the global value chain, thus increasing their sustainability. Along the same lines, Ortigueira-Sánchez et al (2020) found that, for the case of Perú, ACAP is related to innovation. However, González-Campo and Hurtado (2014) found high ACAP levels in Colombian firms, did not determine their innovation outcomes.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 76%
See 1 more Smart Citation
“…Also, Cabrera & González (2019) specify that manufacturing firms interact with external sources of knowledge to improve their capacity for innovation; meanwhile, Heredia et al (2019) sustains that the managers of manufacturing firms develop strategies that are oriented towards reducing costs. Likewise, Ortigueira-Sánchez et al (2020) investigate what factors favor the development of the innovation capacity of Peruvian manufacturing firms. Meanwhile, Seclen-Luna, Regalado & Cordova (2020) indicate that the Peruvian government is financing innovative projects that improve the innovation capability of Peruvian manufacturing firms.…”
Section: Introductionmentioning
confidence: 99%
“…个方面促进数字内容产业发展。佟雪娜(2014) [6] 建议中国音乐影视行业要克服版权保护的障碍,实现 线上线下深度融合,实现各产业链条联动衔接,优化音乐产业链和价值链,推动音乐产业对外贸易提 质增值。陆菁、叶亚露(2018) [7] 基于数字产业贸易的发展现状,从经济理论和实践层面深入分析了数 字化对我国产业结构的推动作用,并构建 VAR 模型,验证了数字贸易对中国产业结构升级具有十分 有效的正向推动作用。曾鹏璇(2018) [8] 探讨了中国数字社交音乐视频行业未来创新发展路径,提出应 创新性地构建以音乐用户内容为服务中心的全球性泛数字音乐社交生态圈,利用新 4C 级的营销策略 迅速打造各大社交音乐平台。 大多学者针对数字经济的未来发展和贸易规制进行分析,也有部分学者从产业升级角度分析数字 经济的助推作用,但仍存在深入探讨的空间。"数字化"驱动的 1.0 时代已经过去,取而代之的是"数据 化"驱动的 2.0 时代。本文将深入分析数字经济 2.0 时代的主要特征,聚焦音乐产业的商业模式,通过 网易云音乐这一典型案例,分析数字经济对音乐产业的影响,并对中国数字音乐产业未来商业模式的 发展提出建议。 二、数字经济促进音乐产业创新重塑 (一)数字经济 2.0 时代的特征 与传统经济相比,数字经济具有数字化、高效率、包容性和整合性四大特征。数字信息传统技术 的快速发展不仅促进了我国信息传统产业的快速发展,也催生了新信息技术产业、新一代信息网络技 术、新网络服务信息产品、新信息服务商等业态的出现 [9] 。数字化带来了产业一体化和生产消费一体 化,新兴产业和新服务业态正在快速兴起,产业链的边界越来越模糊。数字时代的商业模式以广大消 费者群体为需求中心,消费者可以参与电子产品整个价值链的研发、制造和市场营销,实现"生产者+ 消费者"一体化 [10] 1556303107@qq.com, https: //orcid.org/0000-0002-4591-053X 孟方琳,女,1980 年出生,黑龙江人,上海杉达学院副教授,东华大学博士生,Email: mfanglin@163.com, ORCID: https://orcid.org/0000-0002-7769-1220…”
unclassified